Splitting rivers at their seams: bifurcations and avulsion. Issue 1 (6th June 2012) - Kleinhans, Maarten G.; Ferguson, Robert I.; Lane, Stuart N.; Hardy, Richard J.
ABSTRACT: River bifurcations are critical but poorly understood elements of many geomorphological systems. They are integral elements of alluvial fans, braided rivers, fluvial lowland plains, and deltas and control the partitioning of water and sediment through these systems. Bifurcations are commonly unstable but their lifespan varies greatly. In braided rivers bars and channels migrate, split and merge at annual or shorter timescales, thereby creating and abandoning bifurcations. This behaviour has been studied mainly by geomorphologists and fluid dynamicists. Bifurcations also exist during avulsion, the process of a river changing course on a floodplain or in a delta, which may take 10 2 –10 3 years and has been studied mainly by sedimentologists. This review synthesizes our current understanding of bifurcations and brings together insights from different research communities and different environmental settings. We consider the causes and initiation of bifurcations and avulsion, the physical mechanisms controlling bifurcation and avulsion evolution, mathematical and numerical modelling of these processes, and the possibility of stable bifurcations. We end the review with some open questions. Copyright © 2012 John Wiley & Sons, Ltd.